The Unrapeable Black Woman: Understanding The Plight Of The Black Rape Complainant In Contemporary South Africa - Albanie, Zethu (Department of Sociology, 2024)
Despite various research studies on rape investigation and prosecution, as well as the treatment/mistreatment of victims, it remains a concern in South Africa. Victims often hesitate to disclose incidences of sexual violence, and those who do face challenges in being believed or having their cases heard in court. This difficulty arises from the inherent complexity of proving rape, contributing to a pervasive mistrust of rape victims. This issue is particularly troubling for Black women, as the colonial-generated perception of their bodies portrays sexual violence as an expected outcome of their ordinary sexual behaviours, categorising them as supposedly immune to rape. Black women are consequently displaced as victims of rape due to their historic hyper-sexualisation and over-sexualisation. The objective of this thesis is to comprehend the plight of Black rape victims within the criminal justice system. I contend that, due to the myth of the unrapeable Black woman, Black rape complainants must fight for credibility in the eyes of the criminal justice system actors. Stereotypically based judgements continue to negatively impact perceptions and decision-making concerning the rape of Black women. Utilising personal narrative-focused research and sharing my experiences as a Black rape complainant in South Africa, this thesis contends that the criminal justice system's judgements of Black women's rape experiences mirror broader societal attitudes towards rape and race. The study aims to elicit a critical, constructive assessment of the criminal justice system's culture and practices to improve the societal response to victims of sexual violence, thus preventing the miscarriage of justice for Black rape complainants. This study advocates for the decolonisation of the criminal justice system by examining its adherence to colonial ideals. Keywords: Rape, Black women, Unrapeable, Criminal Justice System, South Africa